Can We Help Adolescents Improve Their Mental Health with a Healthy Diet? A Formative Study - Wardle, Christine Mary (Auckland University of Technology, 2023)
Adolescents are overrepresented in current global mental health statistics. As most mental illnesses begin in adolescence, this is likely to increase the burden of mental illness for subsequent generations. Under resourcing of mental health care provision means many adolescents do not receive appropriate care and many cases go untreated. Furthermore, mental health care operates on a deficit model, which creates a dependency paradigm and does not address the causes of poor mental health in this age-group. Although there are multiple causes of poor mental health in adolescents, recent research has found a significant connection between poor diet and mental illness. High consumption of ultra-processed food means adolescent diets, overall, are not meeting the nutritional requirements for optimal brain function. This is causing neurological disturbances which are manifesting in mood disorders, especially anxiety and depression. There is a strong likelihood that therapeutic dietary intervention would significantly reduce the burden of mental illness in adolescents. Eliciting dietary change in adolescents could be challenging. Current research suggests unhealthy eating is driven by impulsivity and risk-taking behaviour which is prevalent in this age-group due to their stage of neurological development. Therefore, we need to determine how dietary behaviour change could be effected in this age-group, either through current health-care providers or by motivating adolescents themselves to make autonomous dietary changes. This thesis used two qualitative formative studies to explore possible scenarios for dietary intervention to promote adolescent mental wellbeing. The first was the potential for school guidance counsellors to incorporate therapeutic dietary intervention into their therapeutic practice; the second was for adolescents to autonomously change their dietary behaviour. The overall aim was to determine the feasibility, and the structural and delivery points of a dietary intervention in the interests of adolescent mental wellbeing. Further aims of the two studies were to understand participants’ knowledge of the relationship between diet and mental wellbeing. Additionally, they determined motivators and barriers to healthy eating and how dietary change could be effected in adolescents in the interests of mental wellbeing. Both studies used the interpretivist theoretical framework. Data were interpreted in relation to recent cohort studies in this field. The following themes (in bold) were constructed from the data using thematic inductive analysis: Study 1: Guidance counsellors’ knowledge of the relationship between diet and mental health was based on inherent beliefs and there was inconsistency between inherent beliefs and professional practice. They were unwilling to use therapeutic dietary intervention because it was not a prescribed therapeutic modality. They also believed that approaching sensitive issues, such as diet, may adversely affect their therapeutic relationships. Guidance counsellors identified that multiple factors influenced adolescent diet. The influence of food marketing and cost were significant barriers to healthy eating. Guidance counsellors believed eating ‘bad’ food was better than no food and it was acceptable to eat everything in moderation. A significant finding was that therapeutic dietary intervention was not within guidance counsellors' scope of practice. Lack of training and professional development meant they were not ready and lacked a remit to give such advice. Therefore, school wide approaches should be used for dietary intervention. Overall, guidance counsellors did not have the necessary skills and knowledge to implement a therapeutic dietary intervention to improve adolescent mental wellbeing. Study 2: Adolescents showed they would make autonomous (autonomy) healthy dietary choices when they were empowered through knowledge about how diet could improve their mental wellbeing. Connecting negative experience to unhealthy eating steered them towards healthier eating. Ethics and heteronomy were also the basis of autonomous choices. Adolescent rebellious tendencies could be directed towards positive dietary behaviour, provided adolescents believed it was beneficial. Autonomous dietary behaviour change was not entirely possible, however, because they were still subject to parental influence. Dietary behaviour change depended on how willing or able parents were to support them. The studies showed dietary intervention was a feasible therapeutic strategy for adolescents with mild to moderate mood disorders; however, delivery was not within guidance counsellors’ scope of practice, knowledge or skill base. Guidance counsellors were not the most appropriate professionals to conduct a dietary intervention. Therefore, it would be necessary to consider alternative providers, potentially outside the school setting. Although adolescents demonstrated they could be motivated to make autonomous healthy dietary choices, overcoming heteronomous barriers to healthy eating was not entirely possible without the support of parents. Future formative research is needed to determine whether parents could support adolescent dietary change. A subsequent phase would involve conducting effective implementation research across multiple settings to determine the efficacy of a dietary intervention in assisting adolescents with mood disorders.